2015
DOI: 10.14300/mnnc.2015.10085
|View full text |Cite
|
Sign up to set email alerts
|

Vitamins concentration after bariatric surgery

Abstract: Обследовали 100 больных с ожирением. Регулируемое бандажирование желудка (РБЖ) было выполнено 20 пациентам, рукавная резекция желудка (РРЖ)-40 больным и гастрошунтирование (ГШ)-40 больным. Контрольную группу составили 10 практически здоровых людей. В сыворотке крови иммуноферментным методом определяли концентрацию витаминов В 1 , В 2 , В 5 , В 6 , В 9 , В 12 , С, D, ниацина, биотина и ретинол-связывающего белка (РСБ) до операции и через 1 год после хирургического лечения. Выявлено значительное снижение витамин… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…When examining a group of patients who underwent GBn, it was found that even before the operation, more than 50% of patients had a deficiency of vitamins C (95%), B 6 (95%), D (80%), and Folate (50%) in blood. 63 In the postoperative period, the number of patients with a deficiency of folic acid and niacin also increased. In the group of patients who underwent LG, vitamins C, D, B 6 , and folate; retinol and niacin were significantly reduced before the operation (in 87.5%, 100%, 92.5%, 87.5%, 52.5%, and 70% of patients, respectively).…”
Section: Mixed Restrictive and Malabsorptive Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…When examining a group of patients who underwent GBn, it was found that even before the operation, more than 50% of patients had a deficiency of vitamins C (95%), B 6 (95%), D (80%), and Folate (50%) in blood. 63 In the postoperative period, the number of patients with a deficiency of folic acid and niacin also increased. In the group of patients who underwent LG, vitamins C, D, B 6 , and folate; retinol and niacin were significantly reduced before the operation (in 87.5%, 100%, 92.5%, 87.5%, 52.5%, and 70% of patients, respectively).…”
Section: Mixed Restrictive and Malabsorptive Proceduresmentioning
confidence: 99%
“…In the group of patients who underwent GBy, there was a significant decrease in vitamins C, D, B 6 , and folate and retinol Nutrition Today ® both before and after surgery. 63 The authors surmise the niacin deficiency revealed in most patients to be associated with the fact that when performing the above operations that the anatomy of the stomach and the proximal small intestine gets changed, where this vitamin is absorbed. The authors associate the folate deficiency in patients who have undergone GBn and LG with the "termination" of the stomach from the process of folic acid assimilation.…”
Section: Mixed Restrictive and Malabsorptive Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…По результатам исследования с участием 114 пациентов с МО (37 пациентов с ИМТ >50 кг/м 2 и 77 пациентов с ИМТ <50 кг/м 2 ) было показано, что в 78% случаев у пациентов со сверхожирением установка ВЖБ позволяет добиться значительного снижения рисков при проведении хирургической операции [12] [13,14]. После проведения бариатрических операций дефицит витаминов и микроэлементов связан с резким урезанием количества потребляемой пищи и уменьшением зоны всасывания [15]. При этом он наиболее выражен после БПШ [16].…”
Section: установка внутрижелудочного баллона (вжб)unclassified